How accurate is telephone triage in out-of-hours care? An observational trial in real patients. Issue 2 (4th March 2022) - Morreel, Stefan; Colliers, Annelies; Remmen, Roy; Verhoeven, Veronique; Philips, Hilde
ABSTRACT: Objectives: Patients in Belgium needing out-of-hours medical care have two options: the emergency department (ED) or a general practitioner (GP) on call. Currently, there is no triage system in Belgium, so patients do not know where they should go. However, patients who could be managed by a GP frequently present themselves at an ED without referral. GPs often organise themselves in a General Practitioners Cooperative (GPC). This study assesses the accuracy of a newly developed telephone triage guideline. Methods: Observational real-time simulation: all walk-in patients at two GPCs and three EDs were asked to call a triage telephone number with their current medical problem. The operator handling this call registered an urgency level and a resource (ED, GP or ambulance) to deploy. The treating physician's opinion was used a the gold standard for correct triage. Patients were not informed about the outcome of the triage and continued the standard care path they had chosen. Results: The overall sensitivity of the telephone triage for detecting patients who could be managed by a GP was 82% with a specificity of 53%. The correctness of the advice given by the operator according to the physicians was 71%, with 12% underestimation of urgency and 17% overestimation. At the GPC, the sensitivity for detecting patients requiring GP management/care was 91% with a specificity of 36%. At the ED, the sensitivity for detecting GP patients was 67% with a specificity of 48%. Conclusion: This study evaluates a new guideline for telephone triage, showing potential overtriage for patients wanting to attend the GPC, with possible inefficiency, and potential undertriage for patients wanting to attend the ED, with possible safety issues.